Genetic defect of the sodium‐dependent multivitamin transporter: A treatable disease, mimicking biotinidase deficiency - Schwantje, Marit (JIMD Rep, 2019)
The sodium‐dependent multivitamin transporter that facilitates the uptake of the water‐soluble vitamins biotin, pantothenic acid, and the vitamin‐like substance lipoate is coded by the SLC5A6 gene. Variants in this gene cause a relatively novel treatable metabolic disorder. Here we describe the second case. A 17‐month‐old girl presented with hypoglycemia (2.0 mmol/L) and severe metabolic acidosis (pH 6.87), leading to resuscitation. Her history revealed feeding problems from birth and poor weight gain. Metabolic investigation showed elevated plasma C3‐carnitine and C5‐OH‐carnitine. Urine analysis showed persistently elevated excretion of 3‐OH‐isovaleric acid. Biochemically, the combination of elevated C5‐OH‐carnitine and increased excretion of 3‐OH‐isovaleric acid seemed compatible with biotinidase deficiency. Supplementation with biotin was started. Biotinidase activity in plasma showed only marginally decreased activity, which was considered insufficient explanation for her clinical symptoms. Subsequent trio‐based whole exome sequencing revealed compound heterozygosity for variants in the SLC5A6 gene. Upon increasing the dosage of biotin supplementation and introduction of pantothenic acid supplementation, a striking clinical improvement was seen.